The Effectiveness of Sama'iy Therapy as a Method to Improve Healthy Friendship Behavior in Adolescents (Case Study on Adolescents at the Manggis Integrated Health Post, Sukamiskin Village, Arcamanik District, Bandung City): Efektivitas Terapi Sama’iy Sebagai Metode Untuk Meningkatkan Perilaku Pertemanan Yang Sehat Pada Remaja (Studi Kasus Pada Remaja Di Posyandu Manggis Kelurahan Sukamiskin Kecamatan Arcamanik Kota Bandung) - Muhtar Gojali; Hasan Mud'is; Hana Hamidah; Tamami Tamami (Syifa al-Qulub : Jurnal Studi Psikoterapi Sufistik, 2025)
Adolescents experience many changes taht affect the way they interact socially. Issues in teenage freindships often have a negative impact on their development. This study aims to measure the effectiveness of Sama’iy Therapy in fostering healty freindships. Sama’iy Therapy is methos that uses audio to cultivate empathy and self-reflection. The researcj was conducted at Posyandu Manggis, Sukamiskin Subdistrict, Bandung City. A mixed method approach was used, combining both quantitative and qualitative methods. The “I’m Safe For You” module was utilized in psychoeducation as an intervention for freindship behavior. Out of 20 respondents, 12 showed improvement in healthy freindship behavior. Validity and reliability test indicated that the measurement instruments used were accurate and consistent. The result demonstrate that Sama’iy Therapy is effective as a sociall interventio for adolesents